Efectos de un emisario submarino de aguas “residuales” urbanas sobre comunidades de octocorales (Octocorallia: Alcyonacea) en Cuba - Hernández Muñoz, Darlenys (2008)
The composition and structure of octocoral communities on coral reefs close to a submarine outfall were studied at Reparto Flores, west of Havana City, Cuba. Octocoral community changes after the deployment of the submarine outfall in 2000 were monitored from June 2002 to September 2005, taking as baseline the data existing before its construction. The area also receives the influence of the polluted river Quibú that passes through a great part of the west side of the City. Sampling was done by means of SCUBA diving, counting and identifying colonies in situ within a 1 m2 frame that was randomly placed as many times as to warrant stabilized values of Shannon and Weaver’s heterogeneity index H’. In agreement with the available hydrochemical information, changes in the diversity indexes (Shannon and Weaver`s heterogeneity index H’, Pielou’s equitability index J’, and Margalef’s species richness index R1), the Herrera-Moreno’s comparative pol-lution index (ICC), and density of some octocoral species at a depth of 10 m suggest a decrease in the influence of polluters from 1989 to 2005. Nevertheless, these indicators were affected in 2004 by a sudden intense but brief colonization of Briareum asbestinum, a species that is not typical of polluted places. At a depth of 20 m, a co-dominance of Plexaura kuekenthali and Eunicea clavigera (resistant and non resistant to pollution, respec-tively) and an increase of the comparative pollution index (ICC) was observed. The increase of P. kuekenthali, a pollution indicator, suggests a rise in the pollution effect 20 m in depth, because of the recent impact caused by the greater closeness of the outfall mouth 50 m deep. Results corroborate the hypothesis about the pollution indicator character of P. kuekenthali. However, this could not be explored for Eunicea flexuosa (also considered a pollution-indicator) due to an intensive illegal selective extraction for lucrative handicraft purposes, which led to a remarkable decrease in its density. B. asbestinum and E. clavigera were outlined as poorly resistant to pollution.